Current view on alveolar coagulation and fibrinolysis in acute inflammatory and chronic interstitial lung diseases - Wygrecka, Malgorzata; Jablonska, Ewa; Guenther, Andreas; Preissner, Klaus T.; Markart, Philipp (Thrombosis and Haemostasis, 2008)
Acute inflammatory and chronic interstitial lung diseases are characterized by excessive and persistent fibrin deposition in the lung.Intraalveolar fibrin accumulation,observed under these conditions, arises from a leakage of plasma proteins (including fibrinogen) into the alveolar space in combination with a disbalance of alveolar haemostasis. Tissue factor in association with factor VIIa and inhibition of urokinase by plasminogen activator inhibitor-1 are major factors that are responsible for the procoagulant and antifibrinolytic state. In addition, in acute respiratory distress syndrome (ARDS) patients, factor VII-activating protease and extracellular RNA, which may be released into the extracellular milieu from damaged cells during lung injury, may contribute to fibrin formation as well. Fibrin itself can increase vascular permeability, influence the expression of inflammatory mediators and alter the migration and proliferation of various cell types. Additionally, fibrin may inactivate pulmonary surfactant and provide a matrix on which fibroblasts can migrate and produce collagen.Furthermore,cellular activities of haemostatic proteases may also contribute to proinflammatory and fibrotic processes in the lung.The application of coagulation inhibitors, like tissue factor pathway inhibitor, active site-inactivated factor VIIa, activated protein C, antithrombin, heparin or hirudin turned out to be beneficial in experimental models of acute and chronic lung injury. However, the ability of anticoagulant and profibrinolytic agents to improve clinical outcome remains to be elucidated. In the current article, the role of the alveolar coagulation and fibrinolysis systems in acute inflammatory and chronic interstitial lung diseases is discussed with regard to pathomechanisms and modalities of intervention.
Keywords: Coagulation factors; coagulation inhibitors; fibrinogen / fibrin; haemostasis; lung